Peran Guru Sekolah Dasar dalam Menumbuhkan Jiwa Kewirausahaan Anak di Masa Pandemi Covid-19 - Rochiyanti, Ana; Mawardi, Imam (Prosiding University Research Colloquium, 2021)
This research is a qualitative descriptive research, by providing an overview of the cultivation of an entrepreneurial spirit in SD Negeri 1 Purwojati. The research technique was carried out in two ways, namely interview and documentation techniques. While the data analysis technique with descriptive analysis. The result showed that the teachers of SD Negeri 1 Purwojati instilled an entrepreneurial spirit by incorporating entrepreneurial values into learning and providing some skills to make useful objects from objects aroundthem. The entrepreneurial values that are instilled are: 10 innovative; 2) hard work; 3) leadership; 4) tenacious; 5) dare to take risks; 6) commitment; 7) reality ; and 8) communicative